Demokratiebildung für mehr Inklusion mit Fokus auf soziale Benachteiligung - Pausch, Markus (Review of ecumenical studies, 2024)
The fact that citizenship education is considered a task of democratic states is nothing new. Since the end of the Second World War, it has developed and professionalised considerably in many countries. It takes place mainly, but not only, in the education system. In recent years, new questions have arisen in the face of a global crisis of democracy. One of these is the task of democracy education, in promoting the inclusion of people who are disadvantaged for various reasons. In this article, various facets of this task are discussed and conceptually structured.